Edukasi Pemberantasan Jentik Nyamuk dengan Metode G1R1J untuk Cegah DBD di Desa Glah Maunasah Baro. - Urip Pratama; Ellyza Fazlylawati; Icha Nanda Armaya; Deswitia Maharani; Alami Purnama; Nur Illya Fadilla; Putri Fadhillah; Putri Latania Filla; Putri Zakiya; Nazarudin Lembong; Ahmad Danil Kombih; Raihan Daffa Ernanda; Nika Safira; Salsabila Salsabila (Lembaga Pengembangan Kinerja Dosen, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted through the bite of Aedes aegypti or Aedes albopictus. This mosquito is a fast-growing mosquito and causes nearly 390 million people to be infected every year. The symptoms of Dengue Hemorrhagic Fever are similar to dengue fever. Dengue Hemorrhagic Fever has several other symptoms such as continuous heartburn, bleeding in the nose, mouth, gums, and bruising on the vector's skin. Dengue Hemorrhagic Fever (DHF) is an infectious disease that often causes outbreaks and causes death, especially in children. The One House One Jumantik Movement (G1R1J) is community participation and empowerment by involving every family in examining, monitoring and eradicating mosquito larvae to control vector-borne diseases, especially dengue fever, through the cultivation of 3M PLUS Mosquito Nest Eradication.